A nonlinear physics model based on extended synergetics for the flow of infant actions during infant-mother face-to-face communications - Frank, Till (International Journal of Scientific World, 2014)
The temporal ordering or flow of infant actions in the context of infant-mother face-to-face communications is discussed from a nonlinear physics perspective. The actions are considered as spatio-temporal patterns that emerge due to self-organization. The presence of a particular action is described in terms of a finite amplitude of the respective pattern. In line with benchmark models from synergetic sand population dynamics, nonlinear amplitude equations that determine the evolution of the infant actions are defined. The model is extended to take self-inhibition and forgetting into account. More precisely, it is shown that the flow of infant actions during infant-mother communications can be explained by assuming that the infant behavior inhibits itself such that after a certain period of time the performed behavior becomes unstable and a transition towards a new behavior occurs. The proposed model is applied to literature data about Three minute periods of infant-mother face-to-face communications. Since the model parameters determine the characteristic properties of the flow of infant actions, the conclusion is drawn that changes of the flow characteristics observed on the behavioral level during infant development correspond to changes of parameters on the neurobiological level that happen on the relative slow time scale of infant maturation Keywords: Use about five key words or phrases in alphabetical order, separated by commas.